Technologies for teaching DHI students using Libras: a systematic review - Silva, Antônio Carlos de F.; Barbosa, Weider A.; Rodrigues, Cássio L.; Ferreira, Deller J. (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2016: Anais do XXVII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2016.747, 2016)
The Sign Language (SL) is not limited to communication, it is also important for learning, access to information, cultural and social interactions. This paper presents a Systematic Literature Review (SR) in order to identify the technologies that support the teaching of Deaf and Hearing Impaired (DHI) students by means of Brazilian Sign Language (Libras). We have found technologies that are applied on different courses and contexts, highlighting the importance of SL in education. Considering the technologies analyzed in this SR, educational games stand out, while applications for Web content access from mobile devices are not regarded. During this SR, we analyzed 105 papers and the results show that there is a need to develop applications to support the education of DHI.